The Relationship between anxiety, stress, depression, and insomnia in migrant students during the COVID-19 pandemic - Dessy Wahyuni; Sulistyani Sulistyani; Erna Herawati; Retno Sintowati (Universitas 'Aisyiyah Yogyakarta, 2023)
Various conditions that occurred during the COVID-19 pandemic in Indonesia had a psychological effect on the community. This is because the COVID-19 pandemic is a severe stressor. Mental health disorders that occur during a pandemic include anxiety, stress, depression, and insomnia. The purpose of the study was to determine the relationship between levels of anxiety, stress, and depression with the degree of insomnia in overseas students during the COVID-19 pandemic. This study used an observational analytic method with a cross-sectional approach. The sampling technique used in this study was probability sampling with simple random sampling on overseas students in Yogyakarta. The data obtained were analyzed using the chi-square and logistic regression tests with the SPSS program. Based on the chi-square test, the results showed that there was a relationship between anxiety, stress, depression on insomnia, each having a p-value of 0.012, 0.001, and 0.000. The results of the logistic regression test on the variables of anxiety, stress, and depression obtained an R-Square value of 0.455. This value means that the variables of anxiety, stress, and depression influence 45.5% of insomnia disorders. Thus, the levels of anxiety, stress, and depression affect the degree of insomnia of overseas students during the COVID-19 pandemic. Therefore, positive activities and psychological and physical health consultations are needed by overseas students to reduce levels of anxiety, stress, and depression that lead to insomnia during the pandemic.